The Influence of Perceptions of Tax Fairness and Detection Rate on Tax Evasion - Nurmalasari, Widya Indah; Purnomolastu, Nobertus; Pratama, Natasha Lusia; Fransiska, Ninda Bella (International Journal of Science and Society, 2024)
With increasing public needs every year, the government through the Directorate General of Taxes (DJP) strives to always improving tax revenues by reforming the implementation of the tax system. However, in reality the tax collection process is still not running optimally due to a poor tax administration system accompanied by various tax violations such as Tax Evasion. There are several factors that influence Tax Evasion, such as Perception of Tax Fairness and Detection Rate. The research seeks to analyse the influence of Tax Fairness Perceptions and Detection Rate on Tax Evasion. The research uses a quantitative research approach with data collection techniques through distributing questionnaires. The research population is taxpayers in Surabaya with a sample of 100 people. The research data analysis technique was carried out using SEM PLS. The research results prove that Perception of Tax Fairness and Detection Rate have a significant positive influence on Tax Evasion.